Bitter crossing : a Peyton Cote novel - Keeley, D. A., 1970- (Woodbury, Minnesota : Midnight Ink, 2014)
Having spent the last seven years in Texas, Border Patrol Agent Peyton Cote is returning home to northern Maine, hoping it will be a safer environment for her young son. But the criminal element has turned what was once a quiet corner of the country into an illicit trade route...and there's no telling what they'll do to protect their interests. When Peyton finds a baby abandoned in a frozen field near the border, she's pulled into a deadly conspiracy that puts everything-her life, her career, her family-at risk.
Keywords: Border patrol agents -- Fiction; Smuggling -- Fiction; Abandoned children -- Fiction; Detective and mystery fiction